DEVELOPMENT POSSIBILITIES OF THE HOSPITALITY SECTOR BY CREATING AND PROMOTING AUTHENTIC TOURIST EXPERIENCES - Mariana PREDA (ALEXE); Liviu MARCUTA; Alina MARCUTA; Andrei Stefan VASILE; Mihaela STANCIU (ONEA) (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study on developing the hospitality sector through the creation and promotion of authentic tourism experiences used a mixed approach with quantitative and qualitative methods to gain a complex insight into tourist preferences. Through questionnaires and interviews, the research collected data from tourists staying in the Sf. Nicolae Alunis guesthouse in Prahova County and at the Casa Romaneasca Hotel in Vâlcea County, Romania. The questions addressed tourists' interest in authenticity, personalization and sustainability in their tourism experiences, providing a basis for better understanding how offerings can be tailored to meet their needs. The results highlighted that most tourists value authenticity in tourism experiences, preferring activities that allow them to discover local culture and interact directly with the community. Personalization was also considered important, with tourists showing interest in activity recommendations and itineraries tailored to their interests. However, the level of interest in customization and authenticity varies, which demonstrates the need for flexible options that allow each tourist to customize their experience according to their own preferences. Another key aspect is supporting sustainable practices. Although many tourists are willing to pay extra for environmentally friendly accommodations, price sensitivity remains an important factor. This involves a balance between meeting ecological requirements and maintaining price competitiveness. In conclusion, the study shows that the hospitality sector can benefit significantly from the integration of authenticity, personalization and sustainability in the offer, aspects that contribute to increasing tourist satisfaction and loyalty.